Right place of human resource management in the reform of health sector. - Seyed Abas Hassani; Hossein Mobaraki; Maboubeh Bayat; Shiva Mafimoradi (Tehran University of Medical Sciences, 2013)
In this paper the real role and place of human resource (HR) in health system reform will be discussed and determined within the whole system through the comprehensive Human Resource Management (HRM) model.Delphi survey and a questionnaire were used to 1) collect HR manager ideas and comments and 2) identify the main challenges of HRM. Then the results were discussed in an expert panel after being analyzed by content analysis method. Also, a deep focus study of recorded documents related to Health Human Resource Management was done. Then based on all achieved results, a rich picture was drawn to illustrate the right place of HRM in health sector. Finally, the authors revitalize the missed function of HRM within the health sector by drawing a holistic conceptual model.The most percentage of frequency about HR belongs to "Lack of reliable HR information system" (91%) and the least percentage of frequency belongs to "Low responsibility of HR" (28%). The most percentage of frequency about HR manager belongs to "Inattention to HR managers as key managers and consider them in background" (80%) and the least percentage of frequency belongs to "Lack of coordination between universities' policies" (30%). According to the conceptual framework, human resources employed in health system are viewed from two comprehensive approaches: instrumental approach and institutional.Unlike the common belief that looks HRM through the supportive approach, it is discussed that HRM not only has an instrumental role, but also do have a driver role.